2012
DOI: 10.1186/1471-2156-13-43
|View full text |Cite
|
Sign up to set email alerts
|

Linkage disequilibrium and inbreeding estimation in Spanish Churra sheep

Abstract: BackgroundGenomic technologies, such as high-throughput genotyping based on SNP arrays, have great potential to decipher the genetic architecture of complex traits and provide background information concerning genome structure in domestic animals, including the extent of linkage disequilibrium (LD) and haplotype blocks. The objective of this study was to estimate LD, the population evolution (past effective population size) and the level of inbreeding in Spanish Churra sheep.ResultsA total of 43,784 SNPs distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
69
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(85 citation statements)
references
References 42 publications
12
69
3
1
Order By: Relevance
“…However, it should be Runs of homozygosity in three local cattle breeds underlined that some parameters, as density and frequency of SNP pairs and distribution of MAF, affect the estimations of LD (Ober et al, 2013) and then of N e . Moreover, the methods used to convert physical distances between SNP pairs to genetic distance may result in different estimated N e values (García-Gámez et al, 2012). Estimate of N e obtained in this study for Italian Holstein was closed to those previously published for other Holstein population (Rodríguez-Ramilo et al, 2015).…”
Section: Resultscontrasting
confidence: 47%
“…However, it should be Runs of homozygosity in three local cattle breeds underlined that some parameters, as density and frequency of SNP pairs and distribution of MAF, affect the estimations of LD (Ober et al, 2013) and then of N e . Moreover, the methods used to convert physical distances between SNP pairs to genetic distance may result in different estimated N e values (García-Gámez et al, 2012). Estimate of N e obtained in this study for Italian Holstein was closed to those previously published for other Holstein population (Rodríguez-Ramilo et al, 2015).…”
Section: Resultscontrasting
confidence: 47%
“…Although the values were not consistent across the chromosomes, LD estimates were slightly greater for longer chromosomes compared to shorter chromosomes. Differences in LD among chromosomes have been reported in cattle (Khatkar et al 2008;Lu et al 2012) and sheep (García-Gámez et al 2012). These differences might be attributed to variation in autosomal recombination rates, genetic drift and selection influences (Arias et al 2009;Qanbari et al 2010).The variation in LD across autosomal chromosomes implies that LD estimates based on a limited number of chromosomes are likely to be inaccurate (Khatkar et al 2008).…”
Section: Discussionmentioning
confidence: 94%
“…Our findings can be compared directly with results from other studies conducted using a similar LD measure and SNP panel. For example, García-Gámez et al (2012), in Spanish Churra sheep, reported an average r 2 of 0.061 for SNPs separated by 200 to 500 kb. Mastrangelo et al (2014) reported an average r 2 for adjacent SNP pairs of 0.155, 0.156 and 0.128 in the Valle del Belice, Comisana and Pinzirita breeds, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The application of recently developed genomic technology has great potential to increase our understanding of the genetic architecture of complex traits, to improve selection efficiency in domestic animals through genomic selection, and to conduct association studies (García-Gámez et al, 2012). The success of these applications depends on the extent of linkage disequilibrium (LD) across the genome.…”
Section: Introductionmentioning
confidence: 99%